Relationship between Mathematics Self-Efficacy (MSE) and Mathematics Self-Regulated Learning Strategies (MSRLS) Among Secondary School Students - Chung, San San (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Mathematics Self-Efficacy (MSE) is an individual’s confidence towards accomplishments of a variety of tasks, ranging from understanding of concepts to problem solving in mathematics. Mathematics Self-Regulated Learning Strategies (MSRLS) is an academically effective form of learning, through which the learner sets the goals; monitors and regulates his or her cognition, motivation and behaviour during the learning process. This research highlights the importance of MSE, MSRLS and the relationship between MSE and MSRLS in teaching and learning of mathematics in school. In addition, the differences in MSE and MSRLS between gender and academic stream are also discussed. The samples in this study consisted of 211 students from Form Four Science and Arts Classes at two secondary schools, Lundu Secondary School and Sematan Secondary School in Lundu, Sarawak. Two research instruments were used to collect data in this study namely Students’ Mathematics Self-Efficacy (MSE) and Students’ Mathematics Self-Regulated Learning Strategies (MSRLS). This study was conducted using a Cross-Sectional Survey research design. Independent samples t-tests were used to determine the differences in MSE and MSRLS based on gender and academic stream. Pearson’s Moment Correlation Coefficients (r) were used to measure the relationships between MSE and MSRLS. The finding from the present study reported no significant difference in MSE and MSRLS based on gender. In addition, finding indicated students’ MSE did not differ significantly between science and arts stream. Nevertheless, there was significant difference in MSRLS based on academic stream. Furthermore, positive and strong relationships were found between MSE and MSRLS.